Developing Workshops to Enhance Hope Among Patients With Metastatic Breast Cancer and Oncologists: A Pilot Study. Issue 6 (June 2021) - Shah, Mirat; Ferguson, Anna; Corn, Phyllis Dvora; Varadhan, Ravi; Ariely, Dan; Stearns, Vered; Smith, B. Douglas; Smith, Thomas J.; Corn, Benjamin W.
Abstract : PURPOSE: Hope is a modifiable entity that can be augmented. We evaluated the feasibility, acceptability, and efficacy of a short intervention to increase hopefulness in patients with advanced breast cancer and oncologists. METHODS: We enrolled eligible participants to two cohorts: one for patients with metastatic breast cancer and one for medical, radiation, or surgical oncologists. The intervention, a half-day hope enhancement workshop, included groups of 10-15 participants within each cohort. Participants in both cohorts completed preworkshop, postworkshop, and 3-month evaluations, which included the Adult Hope Scale (AHS), Herth Hope Index (HHI), and Patient-Reported Outcomes Measurement Information System-Global Health (PROMIS-GH) measures in patients, and the AHS, HHI, and a burnout self-assessment tool in physicians. RESULTS: We consented 13 patients and 26 oncologists for participation in the workshop and 76.9% (n = 10) of consented patients and 100% (n = 26) of consented physicians participated. Postworkshop, all participants planned to incorporate what they learned into their daily lives. In patients, AHS scores increased from preworkshop to postworkshop, and the mean change of 5.90 was significant (range 0-15, SD: 4.7, t = 3.99, P = .0032). HHI scores also increased, although the mean change was not significant. AHS and HHI scores did not significantly change in oncologists from preworkshop to postworkshop. At 3 months, less than half of the participants responded to the evaluation. CONCLUSION: We found that conducting a hope-enhancement workshop for patients with metastatic breast cancer and oncologists was feasible, generally acceptable to both populations, and associated with increased hopefulness in patients. Next steps should focus on confirming this effect in a randomized study and maintaining this effect in the postworkshop interval.